2016
DOI: 10.1186/s13643-016-0370-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of psychostimulants for amphetamine and methamphetamine use disorders: a systematic review and meta-analysis

Abstract: BackgroundAmphetamine and methamphetamine use disorders are associated with severe health and social consequences. No pharmacological therapy has been approved for the treatment of these disorders. Psychostimulants can act as maintenance-like therapies for managing substance use among these patients.The aim of this study is to evaluate the literature examining the efficacy and safety of psychostimulant agents for increasing abstinence and treatment retention among patients with amphetamine and methamphetamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 38 publications
2
41
0
1
Order By: Relevance
“…However only five studies were included in this subgroup analysis. Authors found no effect on treatment retention, but a small subgroup analysis suggested improvement with longer duration of psychostimulant treatment [37].…”
Section: Plos Onementioning
confidence: 96%
See 1 more Smart Citation
“…However only five studies were included in this subgroup analysis. Authors found no effect on treatment retention, but a small subgroup analysis suggested improvement with longer duration of psychostimulant treatment [37].…”
Section: Plos Onementioning
confidence: 96%
“…It is hypothesized that psychostimulant treatment for stimulant use disorder may be effective by substituting a slow acting drug with a similar mechanism of action, thereby reducing withdrawal symptoms and cravings [36]. Eight reviews and metaanalyses assessing the use of psychostimulants for treatment of stimulant use disorder have been included in this review: four were appraised as core [25,27,36,49], and four have been included as supplementary evidence [37][38][39][40]. Reviews focused on a single medication have been included as sub-categories.…”
Section: Plos Onementioning
confidence: 99%
“…Ainda entre as drogas estimulantes do SNC temos as anfetaminas, essas substâncias são drogas sintéticas que apresentam níveis crescentes de abuso principalmente entre jovens, gerando um problema de saúde pública, uma vez que a partir da primeira exposição pode-se avançar de forma rápida a dependência. Entre elas temos a 3,4metilenodioximetanfetamina, conhecida por MDMA, droga com ação estimulante e alucinógena, denominada popularmente por ecstasy [11][12].…”
Section: Introductionunclassified
“…A recent systematic review found no effect of psychostimulant agents on sustained abstinence or retention in treatment (58). Novel approaches for the treatment of methamphetamineuse disorder include neuroimmune modulators (minocycline, ibudilast), cognitive enhancers (rivastigmine, galantamine, atomoxetine, modafinil, citicoline), vaccines, and oxytocin (59).…”
Section: Pharmacotherapy For Methamphetamine Use Disordermentioning
confidence: 99%